1992
DOI: 10.1111/j.1570-7458.1992.tb01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds from the eggs of Ostrinia nubilalis and Mamestra brassicae having kairomone activity on Trichogramma brassicae

Abstract: In the presence of an extract of Ostrinia nubilalis or Mamestra brassicae eggs, female Trichogramma brassicae exhibited increased rates of upwind locomotion in the tubes of a linear olfactometer. GC and GC‐MS analyses of O. nubilalis and M. brassicae egg extracts revealed the presence of fatty acids, their ethyl esters, and various hydrocarbons. Exposing the wasps to a mixture of the five main saturated hydrocarbons (heneicosane, tricosane, pentacosane, heptacosane and nonacosane) increased the upwind progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…Several studies have shown that it is difficult to reconstitute mixtures that are as attractive as the original mixture (Turlings et al 1990b;Renou et al 1992). In many cases, several of the mixture's components may evoke strong reactions, but these reactions are not equal to the reaction to the natural mix (Elzen et al 1984;Turlings 1990b;Renou et al 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown that it is difficult to reconstitute mixtures that are as attractive as the original mixture (Turlings et al 1990b;Renou et al 1992). In many cases, several of the mixture's components may evoke strong reactions, but these reactions are not equal to the reaction to the natural mix (Elzen et al 1984;Turlings 1990b;Renou et al 1992).…”
Section: Introductionmentioning
confidence: 98%
“…use egg mass kairomones as ques in locating eggs (Frenoy et al, 1992;Renou et al, 1992). One-to 2-d-old egg masses are preferred for oviposition compared with older egg masses (Renou et al, 1992). In treatment 3, ECB eggs were laid after the application of SLAM Ò .…”
Section: Discussionmentioning
confidence: 99%
“…Females responded most readily to a mixture of five synthetic saturated hydrocarbons, although when tested isolated, they had a very low response only to pentacosane. Females of T. brassicae were also found to be responsive to palmitic acid and ethyl palmitate, indicating that different compounds on the host egg may be used for host location (Renou et al 1992). Females of T. ostriniae were shown to respond to accessory glands from mated females besides the extracts and egg masses of the host Ostrinia furnacalis (Guenée) (Bai et al 2004;Yong et al 2007).…”
Section: Volatile Kairomones From Host Eggsmentioning
confidence: 96%